Flexural Behavior of Reinforced Concrete One-way Slabs with Longitudinal Hollows - Al-Bayati, Jawad; Esraa Kh. Mohsin Abuzaid; Mohammed Hashim Mohammed (Journal of Engineering and Sustainable Development, 2024)
This paper presents an experimental investigation of the flexural behavior of reinforced concrete one-way slabs with longitudinal hollows. Hollow ratios (weight reductions) used in this work are 11.43% and 22.86%. Two longitudinal reinforcement ratios (ρ = 0.58 % and 1.03 %) and four steel fibers volumetric ratios (Vf = 0, 0.2, 0.4, and 0.8%), were used. Results show that slabs with longitudinal hollows having weight reduction up to 22.86%, show reductions in strength (ultimate load) up to 32% and toughness (energy absorption) up to 45% and higher deflections compared to corresponding solid slabs. However, these reductions lowered to 27.5% and 24.5%, respectively using 0.8% steel fibers or 6.3% and 25.5%, respectively by increasing longitudinal reinforcement from 0.58% to 1.03%. Furthermore, increasing longitudinal reinforcement from 0.58% to 1.03% along with using 0.4% steel fibers in a hollow slab gives a strength gain of 17.5% with a reduction in toughness of only 9.8% compared to reference solid slab with 0.58% longitudinal reinforcement and 0% steel fibers. Results also showed that hollow slabs offer stiffer load-deflection behavior (lower deflections) and less maximum crack width as longitudinal reinforcement and/or steel fibers.